Semen quality assessment of local katjang and cross-bred (Katjang X German) bucks - Abdullah, R.; Mukherjee, T.K.; Noran, A.M. (1998)
Semen quality was compared between the local Katjang and the cross-bred (local Katjang ♀ × German Fawn ♂) bucks. There were no significant genotypic differences in semen characteristics of concentration (first ejaculate: 6.19 ± 1.30 - versus 6.33 ± 1.40 × 109/ml; second ejaculate: 5.82 ± 1.10 - versus 5.68 ± 1.45 × 109/ml, for Katjang and the cross-breds, respectively), percentage live (first ejaculate: 77.61 ± 1.33% versus 77.81 ± 0.53%; second ejaculate: 81.97 ± 1.59% versus 82.74 ± 0.96%, for Katjang and cross-breds, respectively) and percentage of normal sperms (first ejaculate: 12.54 ± 3.88% versus 26.45 ± 3.83%; second ejaculate: 38.68 ± 3.65% versus 28.54 ± 4.38%, for Katjang and cross-breds, respectively), with the exception of seminal volume and sperm motility. Means of all variables were within the values reported for other goat breeds. In contrast, the differences in semen characteristics between the first and second ejaculations of both genotypes were more distinct, the second ejaculations always had more volume, more normal sperms and better sperm motility but less sperm concentrations. Removing the seminal plasma and replacing it with tris-citrate buffer greatly prolonged the viability of sperms of both genotypes when stored at 5°C. Sperm motility seems to be a good indicator of sperm viability. However, the sperms of the cross-bred bucks withstood the washing process better and their swimming abilities were superior (8.12 ± 0.46 mm/min) when compared to those of the local Katjang breed (5.42 ± 0.49 mm/min). The higher content of calcium ions in their seminal plasma (first ejaculate: 10.5 ± 0.8 versus 10.6 ± 0.8 mg/100 ml; second ejaculate: 15.3 ± 0.8 versus 16.1 ± 0.8 mg/100 ml, for Katjang and cross-breds, respectively) means that in natural matings the sperms of the cross-breds would be at an advantage compared to those of the local Katjang, since calcium ions reportedly initiate acrosomal reactions.